FitSkills: protocol for a stepped wedge cluster randomised trial of a community-based exercise programme to increase participation among young people with disability. Issue 7 (8th July 2020) - Shields, Nora; Willis, Claire; Imms, Christine; Prendergast, Luke A; Watts, Jennifer J; van Dorsselaer, Ben; McKenzie, Georgia; Bruder, Andrea M; Taylor, Nicholas F
Abstract : Introduction: There is a need to develop relevant, acceptable initiatives that facilitate physical activity participation in young people with disability. FitSkills was developed to support young people with disability to exercise. The primary aims are to investigate if FitSkills can be scaled up from a small, university-led programme to run as a larger community-university partnership programme, and to determine its effectiveness in improving physical activity participation and health-related quality of life for young people with disability. The secondary aims are to evaluate cost-effectiveness, changes in attitudes towards disability and other health-related outcomes for young people with disability. Methods and analysis: A stepped wedge cluster randomised trial using a cohort design and embedded health economic evaluation will compare the effect of FitSkills with a control phase. FitSkills matches a young person with disability with a student mentor and the pair exercise together at their local gymnasium for 1 hour, two times per week for 12 weeks (24 sessions in total). One hundred and sixty young people with disability aged 13 to 30 years will be recruited. Eight community gymnasia will be recruited and randomised into four cluster units to have FitSkills introduced at 3-month intervals. Primary (feasibility, participation and health-related quality of life) and secondary outcomes will be collected longitudinally every 3 months from trial commencement, with eight data collection time points in total. The Practical Robust Implementation and Sustainability Model will be used to support knowledge translation and implementation of project findings into policy and practice. Ethics and dissemination: Ethical approval was obtained from the La Trobe University Human Ethics Committee (HEC17-012), Australian Catholic University (2017–63R), Deakin University (2017–206) and the Victorian Department of Education and Training (2018_003616). Results will be disseminated through published manuscripts, conference presentations, public seminars and practical resources for stakeholder groups. Trial registration number: ACTRN12617000766314. Trial sponsor: La Trobe University.